2015
DOI: 10.1186/s12881-015-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of association among clinical features and shorter leukocyte telomere length in mitochondrial diabetes with m.3243A>G mitochondrial DNA mutation

Abstract: BackgroundMitochondrial diabetes is a kind of rare diabetes caused by monogenic mutation in mitochondia. The study aimed to summarize the clinical phenotype profiles in mitochondrial diabetes withm.3243A>G mitochondrial DNA mutation and to investigate the mechanism in this kind of diabetes by analyzing the relationship among clinical phenotypes and peripheral leukocyte DNA telomere length.MethodsFifteen patients with maternally inherited diabetes in five families were confirmed as carrying the m.3243A>G mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A case–control study found TL to be associated with C-peptide ( 10 ), similar results were observed in a cross-sectional study ( 13 ). However, other studies did not find a correlation between TL and C-peptide ( 11 , 12 ). C-peptide is a short polypeptide with 31-amino-acid and relates insulin’s A-chain to its B-chain in the proinsulin molecule.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A case–control study found TL to be associated with C-peptide ( 10 ), similar results were observed in a cross-sectional study ( 13 ). However, other studies did not find a correlation between TL and C-peptide ( 11 , 12 ). C-peptide is a short polypeptide with 31-amino-acid and relates insulin’s A-chain to its B-chain in the proinsulin molecule.…”
Section: Introductionmentioning
confidence: 75%
“…However, its association with C-peptide has seldom been examined. A case–control study with 15 participants did not find a significant correlation between TL and C-peptide ( 11 ). Another study in 52 new infants of mothers with gestational diabetes and pre-gestational diabetes assessed both TL and C-peptide in this sample, but did not extensively examined their association ( 12 ).…”
Section: Discussionmentioning
confidence: 94%
“…This nutrient-induced mitochondrial dysfunction can lead to impaired respiration, lipotoxicity, oxidative species accumulation and inflammation, further exacerbating insulin resistance and type-2 diabetes [ 8 13 ]. Indeed, the importance of adequate mitochondrial function for metabolic health is further highlighted by the observation that mitochondrial DNA mutations often result in diabetic phenotypes [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…LTL determination in patients with diabetes mellitus (DM) has highlighted a significant association with the presence and number of diabetes complications [1921]. Moreover, LTL attrition has also been described in patients with mitochondrial diabetes, suggesting its relevance in the disease [22]. Short leukocyte telomere length predicts risk of diabetes in American Indians [23].…”
Section: Introductionmentioning
confidence: 99%